Zelkovamycin is an OXPHOS Inhibitory Member of the Argyrin Natural Product Family. Issue 39 (17th June 2020) - Krahn, Daniel; Heilmann, Geronimo; Vogel, Felix C. E.; Papadopoulos, Chrisovalantis; Zweerink, Susanne; Kaschani, Farnusch; Meyer, Hemmo; Roesch, Alexander; Kaiser, Markus
Abstract: Natural products (NPs) are an important inspirational source for developing drugs and chemical probes. In 1999, the group of Ōmura reported the constitutional elucidation of zelkovamycin. Although largely unrecognized so far, this NP displays structural similarities as well as differences to the argyrin NP family, a class of peptidic NPs with promising anticancer activities and diverse mode‐of‐action at the molecular level. By a combination of structure elucidation experiments, the first total synthesis of zelkovamycin and bioassays, the zelkovamycin configuration was determined and its previously proposed molecular structure was revised. The full structure assignment proves zelkovamycin as an additional member of the argyrins with however unique OXPHOS inhibitory properties. Zelkovamycin may therefore not only serve as a new starting point for chemical inhibitors of the OXPHOS system, but also guide customized argyrin NP isolation and biosynthesis studies. Abstract : Zelkovamycin is an argyrin natural product. By a combination of structural elucidation methodologies, total synthesis and bioassays, the exact molecular structure of zelkovamycin was assigned and revised and its OXHPOS inhibitory properties revealed.